Drivers' perceptions about the use of mobile phones and seat belts while driving - Benzana, Isaias Benjamim; Maposse, Alfredo Júlio; Mabasso, Quitéria Martins (REVISE - Revista Integrativa em Inovações Tecnológicas nas Ciências da Saúde, 2021)
The present survey study investigated drivers' perceptions regarding the risky behaviors related to the use of cellphone and seatbelt while driving. The research adopted a quantitative approach, involving a sample of 402 participants in the Eduardo Mondlane University Campus, among employees and students, using a dichotomous self-report questionnaire. The results showed that, on the one hand, 41.7% of the participants assumed to use the cellphone while driving and 90.7% considered that this behavior occurs with other drivers. On the other hand, 75.8% of the participants admitted not using seatbelt, while 53% stated that other drivers did not. The research concluded that the reported use of cellphone and seatbelt is a concern for the road safety and requires interventions aiming to prevent these risky behaviors among drivers. However, similar and systematic researches need to be carried out to deepen the different contexts and ways of using the cellphone and seatbelt among drivers.